PENERAPAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTU MEDIA GAMBAR TERHADAP HASIL BELAJAR, KINERJA GURU, DAN AKTIVITAS SISWA ILMU PENGETAHUAN SOSIAL KELAS IV SD - Singgih Adhi P, Lynda Puspita Sari (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2015)
This research is motivated by low yields and social studies teachers do not use a model of learning in learning. The problem in this research is "Is there any application of learning models Contextual Teaching and Learning (CTL) assisted Media Pictures on learning outcomes, teacher performance and student activity IPS sixth grade students of SD Negeri 1 Bugo Jepara?". This study aims to determine the application of learning models Contextual Teaching and Learning (CTL) assisted Media Pictures on learning outcomes, teacher performance and student activity IPS sixth grade students of SD Negeri 1 Bugo Jepara. Results showed hypothesis test obtained thitung price 5.862 1.685 ttable thus thitung> ttable or 5.862> 1.685, the then Ho is rejected and H1 accepted or it can be said that the average difference in initial conditions with final conditions significantly. The conclusion was that there is application of learning models Contextual Teaching and Learning (CTL) assisted Learning Results Media Pictures Against IPS Grade VI Elementary School 1 Bugo Jepara.